Representations of indigenous people in contemporary textbooks - Gomes, Luana Barth; da Silva, Denise Regina Quaresma; Casagrande, Cledes Antonio (Education Policy Analysis Archives, 2020)
This paper presents data from a research on how indigenous people are visually represented in contemporary textbooks. It is a qualitative study with exploratory emphases, based on documental analysis, in the study of images and data collected from Brazilian educational handbooks. The data analysis and interpretation are based on the hermeneutical philosophical tradition. The investigation highlighted that although there are signs of progress in the public policies that make indigenous people visible in our society, there is much improvement needed regarding the visual representation of Amerindians in textbooks, particularly the construction of this identity in the contemporary world that is free from stereotypes, invisibility, and Eurocentrism that exists in society and is reaffirmed in textbooks. The image of indigenous people come from the twisted ideas that we learn when we are in school. This stereotypical projection remains once we are not in touch with materials that portrait these people in the correct way, but also because of the previous mistaken conceptions that people who produce these cultural artifacts have.